Synthesis and Characterisation of Molybdenum- Vanadium Oxide Catalysts Prepared By Reflux Method - Tan, Yee Wean (2007)
Reflux method was used to prepare MoV oxide catalysts for one controlled sample where no additional species was added, then EDTA, hexane, hydrazine sulphate and urea as organic species were added during the synthesis procedure for another 4 samples. The catalysts obtained based on different calcination environment conditions and temperatures have been compared in order to determine their influence on the physicochemical properties of the catalyst. The precursors were characterised using thermogravimetry analysis (TGA) and x-ray diffraction (XRD), and the calcined samples were characterised using XRD, scanning electron microscopy (SEM) and BET surface area measurements (SBET). It has been found that the organic-metal salt complexes facilitate well dispersed, organised structure and high SBET MoV oxide based formation. This is only true for hydrazine sulphate- and urea- metal salt complexes with SBET of 5.5 and 10.9 m2g-1 respectively, as EDTA- and hexane- metal salt complexes lead to aggregated and low SBET oxide formation with the SBET of 0.1 and 1.8 m2g-1 respectively. Catalytic test of the MoV oxide, MoVTe oxide and MoVTeNb oxide shows notable effects of the addition of tellurium and niobium to the molybdenum vanadate matrix. It is found that MoV oxide is sufficiently active for propane selective oxidation to acrylic acid with high conversion percentage of 45 to 62%. When tellurium is added the catalytic activity remains almost constant but the selectivity decreases from 31% to 7%. However, niobium is found to increase the catalyst stability in high heat pre-treatment whereby the quaternary oxides showed better selectivity than the ternary oxides and increases from 7% to 32%. Niobium has a significant role in the insertion of oxygen into the hydrocarbon intermediate, although the metal itself is not part of the crystal system. Thus niobium is needed for the selectivity of the reaction. In overall, the MoV and MoVTeNb is active and selective when bear the mixture of orthorhombic structure where molybdenum is part of the lattice and a phase where vanadium is present.